Disparities in uptake of 13-valent pneumococcal conjugate vaccine among older adults in the United States. Issue 4 (3rd April 2019) - McLaughlin, John M.; Swerdlow, David L.; Khan, Farid; Will, Oliver; Curry, Aaron; Snow, Vincenza; Isturiz, Raul E.; Jodar, Luis
ABSTRACT: Background : In September 2014, 13-valent pneumococcal conjugate vaccine (PCV13) was universally recommended for all US adults aged ≥65 years. Adult PCV13 coverage, including whether disparities in uptake exist, however, is not well-described. Methods : We used a monthly series of cross-sectional analyses of administrative medical and prescription claims data collected by IQVIA and linked to sociodemographic data collected by Experian to estimate overall and subpopulation-level uptake of PCV13 among US adults aged ≥65 years. Results : Among adults aged ≥65 years, 43.3% received PCV13 by the end of November 2017. Race/ethnicity, annual household income, education status, and neighborhood urbanicity were strongly related to PCV13 uptake among adults aged ≥65 years. Lower uptake of PCV13 was observed for non-Hispanic black (36.3%) and Hispanic (30.0%) adults ( vs 45.6% for non-Hispanic whites, P < .01), the poor (30.7% vs 54.2% among lowest vs highest income deciles, P < .01), adults with low educational status (33.0% vs 49.0% among those without high school education vs college educated, P < .01), and those living in rural communities (22.9%) or urban/inner-city (33.8%) areas ( vs 45.8% in suburban areas, P < .01). Conclusions : PCV13 uptake among adults aged ≥65 occurred rapidly in the three years after universal recommendation in September 2014. Yet, poor and minority communities, rural and urban/inner-city areas, and communities with low educational attainment had substantially lower PCV13 coverage. These same populations are at increased risk of pneumococcal disease. In order to maximize the benefits of pneumococcal vaccination, further targeted and tailored interventions to increase PCV13 uptake in these underserved populations are still necessary.